Efeito genômico de bebidas ricas em cafeína e catequinas na modulação de marcadores oxidativos e inflamatórios associados a imunossenescência - Alves, Audrei de Oliveira (2021)
Introduction: Brazil has shown an accelerated aging process when compared to other countries in the world, a fact that directly impacts health and social care systems, as biological aging is associated with dysfunctions that increase the risk of dependence, non-communicable chronic diseases (NCCDs), institutionalization, hospitalization and death. In addition, it reduces the efficiency of the immune response against infection by pathogens, a situation observed in the Covid-19 pandemic, in which the elderly people were the most affected. Epidemiological, clinical and experimental evidence suggests that biological aging could be modulated by environmental factors such as diet, which seems to be able to mitigate relevant physiological changes. Objectives: In this sense, this study aimed to evaluate the genomic effect of aqueous extracts of coffee, black and green teas, yerba mate and guarana in the modulation of oxidative and inflammatory markers. The first study analyzed the inflammatory modulation of non-activated peripheral blood mononuclear cells (na-PBMCs), yeast-activated human neutrophils, and Eisenia fetida earthworm granulocytic coelomocytes. The second study involved two separate protocols. The first one evaluated the inflammatory activation of PBMCs obtained from healthy individuals before and after ingesting 100 mL of each drink, by modulation of reactive oxygen species (ROS). The second protocol involved an in vitro analysis of caffeinated extracts and isolated bioactive molecules caffeine (Caf), theobromine (The) and catechin (Cat) in the modulation of antioxidant enzymes genes such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX). Results: The results of the first study are published in the journal Food and Chemical Toxicology. Immunoassays performed in human PBMCs cultured for 24 hours showed that all extracts decreased the levels of the pro-inflammatory cytokines IL-1β, IL 6, TNF-α and IFN-γ, and increased the levels of the anti-inflammatory cytokine IL-10, in addition to induce an overexpression of their genes. An additional assay, in which human neutrophils with and without treatment to the extracts were exposed to inactivated yeasts, showed that there was an increase in the production of neutrophil extracellular traps (NETs). The analysis of the inflammatory response triggered in earthworms treated with the extracts and exposed to inactivated yeasts corroborated the hypothesis that these beverages improve the immune response in the presence of pathogens, being, however, distinct for each extract, with special emphasis on yerba mate. The second study was submitted to the journal Nutrition and analyzed PBMC cultures before and after the ingestion of extracts, demonstrating a decrease in viability and in nitric oxide (NO) levels after ingestion. The extracts exhibited high similarity in the regulation of antioxidant genes, decreasing their expression. Conclusions: The set of results suggests that caffeinated beverages share bioactive components in their chemical matrix, and have similar action, modulating low-grade chronic inflammatory processes and increasing the competence of acute inflammation triggered by pathogens. Thus, it seems that caffeinated beverages may attenuate immunossenescence processes associated with the dysfunctions and NCCDs prevalent in biological aging.